PRODUCT DESIGN OF MARINE SOLDIER BACKPACK WITH QUALITY FUNCTION DEPLOYMENT METHOD - Arys Susanto; Sri Gunadi; Suprayitno Suprayitno (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2021)
The success of Marines in carrying out the task should be supported by the ability, technique and also sufficient instrument. One of the equipment is the backpack of combat. Which is improved along with the improvement of the age. The availability of soldier combat backpack was considered not comfortable. The intention of this research is to redesign the available combat backpack. It utilizes QFD (Quality Function Deployment) method and also principles of ergonomic which that intended to meet the requirement in solving the available problems. We can get information about any desirable and prioritized attributes by user and also any prioritized technical characteristics in designing this combat backpack by applying QFD. In order to apply the principles of ergonomic, the design of this combat backpack need anthropometric data from the Yon Marine soldier’s body. The undertaken statistical tests are hopefully able to represent the whole population (Yon Taifib soldier). The result of this research is a prototype of the combat backpack. Keywords: Combat Backpack, Quality Function Deployment (QFD), ergonomic